(untitled) (Journal of International Studies, 2018)
States and world institutions have globally recognized the right to quality education. One of the method to access quality education is via Open Educational Resources (OER) that operates under the concept of â€œopennessâ€ where knowledge should be freely shared and disseminated for all. Yet, copyright law appears to be an area of great concern hampering OER development. This paper begins by clarifying the fundamental right to education which can be supported by developing trends of using digital resources. It then describes some of the developments in achieving sustainable development goal towards quality education through OER. The paper then explains certain legal challenges hampering open education initiatives by highlighting relevant copyright laws at the international and domestic levels. This investigation takes the form of a qualitative case-study approach comparing Malaysia and Japan practices in respect of its OER initiatives within their higher education institutions. This study specifically examines related regulations extracted from relevant statutes, cases, reports and secondary sources available in both countries. There appears to be a growing tension between the desire to promote open access to quality education and the need to protect works even though OER may be useful and beneficial for society.